Pengaruh Perbedaan Durasi Waktu Thawing terhadap Tingkat Motilitas dan Tingkat Viabilitas Sperma Beku Kerapu Kertang Epinephelus lanceolatus - Adi Wiranto; Henky Irawan; Muzahar (Intek Akuakultur, 2021)
The production of cryopreserved sperm giant grouper has been successfully carried outto support produced hybrid grouper in Indonesia. Thawing cryopreserved sperm is oneof key to successfully insemination. However, research on the effect of thawing timeof cryopreserved sperm giant grouper (E. lancolatus) on motility rate and viability ratehas not been conducted. This research aims to determine the effect of different durationthawing of cryopreserved sperm giant grouper (E. lanceolatus) on motility rate andviability rate. This research was conducted in December 2020 at Batam MarineAquaculture Fisheries Center, Batam City, Kepulauan Riau Province. The method usedwas experimental completely randomized design (CRD) with 4 treatments and 3replications, namely 3 seconds, 9 seconds, 15 seconds, 21 seconds. Data analysis usedANOVA and Duncan’s continued test showed that the best motility happened in 21seconds (69,99±4,74), the best sperm viability happened in 21 seconds (54,29±1,76).The results obtained indicate that 21 seconds is the best treatment.